Efficacy of pre-and post-emergence herbicides in onion and their carry over effect on the succeeding crops - Rathod, A.D.; Solanki, R.M.; Modhavadia, J.M.; Padamani, D.R. (Annals of Agricultural Research, 2014)
Field experiments were conducted during the rabi seasons of 2007-08 and 2008-09 Junagadh (Gujarat) to study the effect of pre-and post-emergence herbicides for weed management in onion and their persistence. The results indicated that all the treatments reduced the density of major weed species of onion and dry weight of weeds. Growth and yield attributes and bulb yield were increased significantly over unweeded check. Pre-emergence application of pendimethalin 0.9 kgha-1 showed its negative effect on germination, plants height and dry matter accumulation ofindicator plant sorghum at 30 DAS which was disappeared at 60 DAS. Similarly, post-harvest studyon succeeding crops of groundnut, green gram, maize and ladies fingers indicated that there wasno residual phytotoxic effect of either pre- or post- emergence herbicides tested in onion.